2010
DOI: 10.2478/v10102-010-0049-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronic social stress increases nitric oxide-dependent vasorelaxation in normotensive rats

Abstract: The aim of this study was to examine oxidative load and endothelium-dependent vasorelaxation in the serotonin pre-constricted femoral artery (FA) of Wistar-Kyoto (WKY) rats exposed to chronic social stress produced by crowding in the presence or absence of ascorbic acid (AsA) in working solution. Adult male rats were randomly divided into control (living space: 480 cm2/rat) or stressed (living space: 200 cm2/rat) groups for 8 weeks. Blood pressure and heart rate, determined using tail-cuff plethysmography, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…For example, exposing male rats or mice to social stress in the form of chronic crowding [7274] or complex housing conditions [71] has been shown more often to enhance than to impair relaxant responses to ACh in precontracted arteries (including aorta but also femoral arteries). To our knowledge, there are no reports of enhanced endothelium-dependent relaxations in humans with depression or other affective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposing male rats or mice to social stress in the form of chronic crowding [7274] or complex housing conditions [71] has been shown more often to enhance than to impair relaxant responses to ACh in precontracted arteries (including aorta but also femoral arteries). To our knowledge, there are no reports of enhanced endothelium-dependent relaxations in humans with depression or other affective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we observed elevated aortic NOS activity and improved endothelium-dependent relaxation, including its NO-dependent component, in the femoral artery of normotensive rats exposed to crowding (Púzserová et al 2006;Bernátová et al 2007b). Improved NO-dependent relaxation in crowded rats was observed in the femoral artery both in the presence and absence of AsA in working PSS, suggesting no significant influence of oxidative stress on elevated NO level in this artery (Puzserova and Bernatova 2010). Interestingly, the improvement of acetylcholine-induced relaxation in 1MA was seen only in the presence of AsA (Bernátová et al 2007b), while in this study, where AsA was removed, no considerable effect of stress was observed.…”
Section: Discussionmentioning
confidence: 49%
“…After the last acetylcholine concentration, the NO donor sodium nitroprusside (100 μmol/l) was added to the bath to check endothelium-independent NO vasodilator function. The NO-dependent component of endothelium-dependent relaxation was calculated as the difference between acetylcholine-induced relaxation before and after acute L-NAME pre-treatment and expressed as the area under the curve (AUC, arbitrary units) based on individual concentration-response curves (Puzserova and Bernatova 2010). In our preliminary experiments we ruled out tachyphylaxis (Hansen and Nedergaard 1999) in two consecutive concentration-response curves for acetylcholine in phenylephrine pre-contracted 1MA (data not shown).…”
Section: Experimental Protocol For Functional Studies Of the First Brmentioning
confidence: 99%
“…It has recently been shown in animal models that depression-like symptoms are associated with changes in catecholamines homeostasis and endothelial dysfunction in resistance arteries. 76 , 77 , 123 These animal studies grant a unique opportunity to provide mechanistic understanding of cardiovascular abnormalities in association with depression symptoms. Moreover, these studies suggest a mechanism relevant for the unwanted circulatory effects of some antidepressants in depressive patients.…”
Section: Perspectivesmentioning
confidence: 99%